2017
DOI: 10.1021/acsami.7b04100
|View full text |Cite
|
Sign up to set email alerts
|

Template-Mediated Ni(II) Dispersion in Mesoporous SiO2 for Preparation of Highly Dispersed Ni Catalysts: Influence of Template Type

Abstract: Supported Ni catalysts on three mesoporous SiO supports (i.e., SBA-15, MCM-41, and HMS) were prepared using a solid-state reaction between Ni(NO) and organic template-occluded mesoporous SiO. For comparison, supported Ni catalysts on mesoporous SiO synthesized by the conventional impregnation method were also included. The catalysts were characterized by scanning electron microscopy, X-ray diffraction, UV-vis diffuse reflectance spectroscopy, N adsorption, X-ray photoelectron spectroscopy, H temperature-progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Finally, the band gaps of NiO calculated from DRS UV-Vis data were compared to the Ni 0 sizes determined by TEM for the Ni-based catalysts ( Table 3). As reported 47,48 , Ni species size can influence the band gap, since the bigger the particles, the higher the amount of defects and/or vacancies present in the intergranular regions able to generate new energy levels responsible for the reduction of the band gap. Indeed, the results obtained for the samples of the present study confirm the relationship between the Ni 0 sizes and the calculated band gaps for NiO, indicating that the use of different supports influence the electronic properties of the Ni species.…”
Section: Catalysts Characterizationmentioning
confidence: 69%
“…Finally, the band gaps of NiO calculated from DRS UV-Vis data were compared to the Ni 0 sizes determined by TEM for the Ni-based catalysts ( Table 3). As reported 47,48 , Ni species size can influence the band gap, since the bigger the particles, the higher the amount of defects and/or vacancies present in the intergranular regions able to generate new energy levels responsible for the reduction of the band gap. Indeed, the results obtained for the samples of the present study confirm the relationship between the Ni 0 sizes and the calculated band gaps for NiO, indicating that the use of different supports influence the electronic properties of the Ni species.…”
Section: Catalysts Characterizationmentioning
confidence: 69%
“…S1 and S2 † ). 35 , 36 Bulk Pt doped NiO nanocubes were obtained by impregnation, drying and calcination in air, and template removal via NaOH etching, and the nominal Pt loading amount was 0.5 wt%. Such an impregnation & calcination process can be consistently and cost-effectively up-scaled.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the template-containing catalyst displayed a higher catalytic activity, probably due to the presence of strong basic sites, which lead to a major grafting of metal nanoparticles within the silica matrix. Zheng et al [120], studied the same effect in a catalysis for the hydrodechlorination of 1,2-dicholoethane. By contrast to the later report, these authors reported that the strong electrostatic repulsive interactions between Ni (II) and CTAB lead to aggregation of Ni nanoparticles upon calcination resulting in a low dispersion of the nickel source (Ni(NO 3 ) 2 ) into the mesopores of MCM-41.…”
Section: Ruthenium Nanoparticles Supported On Mcm-41mentioning
confidence: 96%